Making international human rights protection more effective: rational-choice approach to the effectiveness of ius standi provisions - Anne van Aaken (Max Planck Institute for Research on Collective Goods, 2005)
Empirical research shows that international human rights law is to a large extent ineffective. Individual complaint mechanisms are the only significantly effective enforcement mechanism. Certainly many variables influence the success of enforcement through judicial or quasi-judicial mechanisms but one important variable are provisions of ius standi as they have a gate-keeping function. International human rights law can be rendered more effective if individual victims have both de jure and de facto access to its remedies. This article analyzes the different incentives provided by complaint mechanisms for individuals, groups or NGOs to make use of international human rights bodies. They are such, that an insufficient enforcement of IHRL can be expected.
Keywords: 340; Menschenrechte; Nichtregierungsorganisation; Rationales Verhalten; Welt